Fikih Kenotariatan: Studi Tentang Etika Profesi Notaris - Miftahul Ulum (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2022)
Law and humans have a close relationship. The existence of law is very important in life, especially in human actions/deeds towards other living creatures. This is because the law is a norm in which there are sanctions. From this definition, it is implied that the existence of law is intended to create order in social life. Laws cannot be enforced without the help of the community and some legal entities. The legal entity in question is the legal profession. The legal profession has many kinds, including: advocates, arbitrators, judges, notaries, prosecutors, police, and legal. Each legal profession has a different purpose and function. They exist to complement the shortcomings of each legal profession. A notary who is one of the legal professions is required to have a good personality. As a public official, a notary must have personal ethics, one of which is the spirit of Pancasila, obeying the laws and regulations in force in the Republic of Indonesia. So crucial and noble is the notary profession, when carrying out his position, he must remain obedient to the applicable regulations, including using an office that has been determined by law, being aware of his obligations, not using mass media, and putting up a nameplate according to the provisions. Hukum dan manusia memiliki hubungan yang erat. Keberadaan hukum sangat penting dalam kehidupan terlebih dalam tindakan/perbuatan manusia terhadap makhluk hidup lain. Hal ini disebabkan hukum merupakan suatu norma yang di dalamnya terdapat sanksi. Dari definisi tersebut sudah tersirat bahwa adanya hukum ditujukan agar terciptanya keteraturan dalam kehidupan bermasyarakat. Hukum tidak dapat ditegakkan tanpa adanya bantuan masyarakat dan beberapa badan hukum. Badan hukum yang dimaksud ialah para profesi hukum. Profesi hukum memiliki banyak macamnya, antara lain: advokat, arbiter, hakim, notaris, jaksa, polisi, dan para legal. Setiap profesi hukum memiliki tujuan dan fungsi yang berbeda. Mereka ada untuk saling melengkapi kekurangan masing-masing profesi hukum.Seorang notaris yang merupakan salah satu profesi hukum dituntut untuk memiliki kepribadian yang baik. Sebagai pejabat umum, notaris wajib memiliki etika kepribadian salah satunya berjiwa Pancasila, taat kepada hukum dan undang-undang yang berlaku di NKRI. Begitu krusial dan mulianya profesi notaris maka ketika melaksanakan jabatannya maka harus tetap patuh pada peraturan yang berlaku diantaranya menggunakan kantor yang telah ditetapkan undang-undang, sadar akan kewajibannya, tidak memakai media massa, dan memasang papan nama sesuai ketentuan.